Gambaran Perilaku Siswa yang Kecanduan Gadget - M. Harwansyah Putra Putra Sinaga; Silvia Hafida Husna Nst; Nurul Husna (Journal on Education, 2023)
This study aims to describe the behavior of students at MTs Negeri 2 Medan. The type of research used in this research is qualitative. Qualitative research is research that is intended to reveal symptoms as a whole and in accordance with the context or what they are through collecting data with a natural background as a direct source with the key research instruments themselves. Data collection tools used are observation, interviews and documentation. The results of the study show that gadget addiction is not only to substances, but also to certain activities that are carried out repeatedly and have a negative impact as well as addiction to gadgets. This will hinder the process of socializing children and will lead to dependence on these gadgets.